B chromosomes in species of the genus Prochilodus (Characiformes, Prochilodontidae): morphological identity and dispersion - Penitente, Manolo [UNESP]; Foresti, Fausto [UNESP]; Porto-Foresti, Fábio [UNESP] (Pensoft Publishers, 2014)
B chromosomes have attracted the attention of Neotropical fish cytogeneticists in recent years, both for their remarkable occurrence in this group and also because of the interest in studies of the genetic structure and role played in the genome of these organisms. The aim of this study was to report the first occurrence of supernumerary chromosomes in Prochilodus argenteus (Agassiz, 1829), this being the fifth carrier species among thirteen within the genus Prochilodus (Agassiz, 1829). The extra elements identified in this species are small sized heterochromatic chromosomes characterized by a low mitotic instability index, being very similar to other supernumerary chromosomes described in the species of the genus Prochilodus. Morphology, structure and dispersion of the supernumerary genomic elements which occur in species of this genus are discussed aiming to better understand aspects involved the origin of supernumerary chromosomes and the differentiation process and relationships among species of this family.
Keywords: Curimbatá; Cytogenetic; Neotropical fish; Supernumerary chromosomes